ANALISIS FOCUS GROUP UNTUK MENDETEKSI DOMAIN CUSTOMER DELIGHT - Raharso, Sri; Amalia, Sholihati (Benefit: Jurnal Manajemen dan Bisnis, 2005)
At the moment customer satisfaction represent norm obliged to given by every organization.Besides, research proves that satisfaction unable to guarantee the happening of customer loyalty.Delight believed by practitioner and academician as construct, which can guarantee customerloyalty. Unhappily, till now research for searching the domain of delight still very rare. Thisresearch tries to search that domain with qualitative technique. Results of focus group yield fivevariables becoming delight domain that are: justice, esteem, security, trust, and variety.